The chemokine receptor CXCR4 is expressed in pancreatic intraepithelial neoplasia. Issue 11 (29th July 2008) - Thomas, R M; Kim, J; Revelo-Penafiel, M P; Angel, R; Dawson, D W; Lowy, A M
Abstract : Objective: The chemokine CXCL12, together with its specific receptor, CXCR4, have been shown to mediate invasiveness and metastatic behaviour in pancreatic cancer cells. The expression of CXC12/CXCR4 has not been previously examined in pancreatic intraepithelial neoplasias (PanIN), the accepted precursor lesions to pancreatic duct cancer. Design: In this study we sought to characterise the expression of CXCL12 and CXCR4 during the progression of PanIN using both a murine model and human tissues. Results: These studies reveal that both CXCL12 and CXCR4 are expressed in PanIN and that the frequency increases during PanIN progression (0% CXCR4 expression in normal mouse and human ducts vs 100% in mouse PanIN 3 and 77% in human PanIN 3). Next we demonstrate a dose-dependent increase in the proliferation of murine PanIN cells when exposed to CXCL12. Finally, we show that expression of CXCR4 in murine PanIN cells is partially dependent on mitogen-activated protein kinase (MAPK) signalling and that the effect of CXCL12 on PanIN proliferation can be abrogated by an MAPK inhibitor. Conclusions: Together these results demonstrate that CXCL12/CXCR4 expression begins in the pre-invasive stages of pancreatic neoplasia, and suggest that the presence of an autocrine loop that is at least partially regulated by MAPK signalling. Further studies that define the role of CXCR4 signalling in PanIN progression will determine if CXCR4 could serve as a novel target for chemoprevention and early stage therapy in pancreatic cancer.